Analysis of The Rejection of Appeals by The Supreme Court in Bankruptcy Cases (Study of Decision Number 374 K/Pdt.Sus-Pailit/2024) - Candice Valerie; Aryya Nannda Wongso; Priscellia Roselyn (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
Bankruptcy serves as a legal mechanism to resolve debt disputes between debtors and creditors in a fair and balanced manner. In Indonesia, it is governed by Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations, which stipulates that bankruptcy may be declared if a debtor has two or more creditors and fails to pay at least one due and collectible debt. However, in practice, bankruptcy proceedings often generate legal controversies that may extend to the cassation stage at the Supreme Court. One notable example is Supreme Court Decision No. 374 K/Pdt.Sus-Pailit/2024, involving PT Multi Inti Karya (Respondent in Bankruptcy) and PT Citra Harda Mandiri (Petitioner in Bankruptcy). This study examines the legal reasoning behind the Supreme Court’s rejection of PT Multi Inti Karya’s cassation request using a normative juridical approach, emphasizing statutory interpretation and judicial analysis. The Court determined that the Central Jakarta Commercial Court had not misapplied the law, as the cassation arguments merely reiterated issues previously assessed by the judex facti, thereby failing to meet the criteria of Article 30 of the Supreme Court Law. Moreover, although the debtor claimed partial debt repayment, the Court found remaining unpaid obligations, satisfying the legal elements for bankruptcy. This decision underscores two key principles: (1) cassation in bankruptcy cases must be based strictly on errors of legal application, not factual repetition; and (2) partial payment does not absolve the debtor’s liability when outstanding debts remain.